Feasibility study of holding the treasury responsible for paying bodily damages incurred by persons without intention to act - Hussein Houshmand Firuzabadi; Ehsan Yavari; Hassan Naqdian (آموزه‌‌های فقه مدني)
According to the rules and principles of civil liability, no damages should remain unclaimed. Where a person has the intention of an action, whether he intends to have a result or not, he is a guarantor in any case, but where a person without complete will and without the intention of the action causes it only for reasons such as hand vibration or instinctual movements while sleeping. The question is whether the guarantor can be changed and the responsibility should be shifted to the government and the treasury, despite the certainty of the guarantee as a status sentence.In this article, exemption without intention to act as a guarantee in inflicting bodily harm due to the lack of causality has been proven as the most important element of civil liability. And secondly, according to one of the channels of payment of zakat, which is "for the sake of God" and the jurists have defined it as payment for the "public benefit of the Islamic society", the guarantor of the payment of personal damages without the intention of action.